Sosialisasi Anti-Bullying dan Pelatihan Microsoft Word pada Siswa Sekolah Dasar di Desa Guyangan, Pati - Putri Kusumawati Priyono; Rina Asih Budi Cahyaningrum; Rizal Fajri; Bayu Hartono (PT. Karya Inovatif Nusantara, 2026)
This community service activity is part of the Collaborative Program of Safin Pati University 2025 in Guyangan Village, Trangkil District, Pati Regency. Two priority programs were implemented for elementary school students: anti-bullying socialization and Microsoft Word training. The aims were to raise students' awareness of bullying behaviors and to improve digital literacy through word processing skills. Methods employed included interactive counseling, group discussion, case studies, and hands-on mentored practice. Anti-bullying socialization was conducted on August 23, 2025, involving 5th and 6th grade students of Guyangan Elementary School. Microsoft Word training was held on August 22, 2025 with the same student cohort. Results indicate improved student understanding of bullying types, prevention strategies, and basic document creation skills using Microsoft Word. Participants responded with high enthusiasm, though challenges included limited computer devices and varying prior skill levels. The program made a meaningful contribution to positive character development and early digital literacy among students.